Geophysical characterization of Udaeta Lake as a possible pull-apart basin associated to quaternary tectonic activity along Magallanes-Fagnano fault system. (20th July 2019) - Onorato, M.R.; Prezzi, C.; Orgeira, M.J.; Perucca, L.P.; Coronato, A.; López, R.; Magneres, I.
Abstract: Pull-apart basins are depressions formed at releasing bends or steps in strike-slip fault systems, between two parallel vertical strike-slip fault sections. In the present study, the geometry of Udaeta Lake, located in the central section of the Magellan-Fagnano Fault System (MFFS) and previously defined by some authors as a pull-apart basin, is analysed. The application of multiple geophysical methods, constrained by surface geological information, enabled us to reveal the subsurface geometry of a section of the MFFS, Udaeta Lake area. Magnetic, gravimetric and detailed topographic profiles, together with vertical electrical soundings were surveyed. The obtained results were compared with fieldwork data. This combined methodology allowed the identification of a transtensional zone with two E-W main sinistral strike-slip faults with a normal component that control the North and South coasts of the lake. This central depression occupied by the lake, with a depth of ∼30 m, is also affected by inferred NE subparallel faults. The geophysical characterization of the MFFS also supports the influence of this fault system on the formation of some water bodies located along the fault zone. Finally, in spite of the lack of detailed geological and structural data, Udaeta Lake we suggest a genesis consistent with a pull-apart basin model. This work constitutes an important contribution to understand earthquake rupture parameters and pattern of surface and in-depth deformation and so, improve knowledge of the seismological behaviour of the MFFS.